The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1111/j.1365-2591.1993.tb00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the success of conventional root canal therapy—a five‐year retrospective study

Abstract: This retrospective study on the outcome of conventional root canal therapy was carried out on patients attending the Eastman Dental Hospital between 1970 and 1982. A minimum follow-up period of 5 years was required for patients to be included in the survey. The characteristics of the resulting sample group, the techniques for canal preparation and obturation and the obturating materials used were analysed. The type of obturating material used had no demonstrable effect on success rate but sex, age, preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
205
1
12

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(247 citation statements)
references
References 31 publications
(9 reference statements)
9
205
1
12
Order By: Relevance
“…There was an obvious, but small, decrease in the size of the lesion during the majority of the follow-up period and as previously reported provided there is a continuous decrease in the size of the lesion there is no need to judge a case a failure. 2 However, it may have been justifi ed in 1997, three years after obtu ration to consider the tooth for surgical treatment as a significant well defi ned radiolucency still remained. Using the PAI scoring system 7 the case presented remained PAI 4 for some time and prob ably did not become a PAI 3 (deemed successful treatment) until seven years after completion of treatment and there fore, under certain circumstances, could have been re-treated if such guidelines were followed closely.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There was an obvious, but small, decrease in the size of the lesion during the majority of the follow-up period and as previously reported provided there is a continuous decrease in the size of the lesion there is no need to judge a case a failure. 2 However, it may have been justifi ed in 1997, three years after obtu ration to consider the tooth for surgical treatment as a significant well defi ned radiolucency still remained. Using the PAI scoring system 7 the case presented remained PAI 4 for some time and prob ably did not become a PAI 3 (deemed successful treatment) until seven years after completion of treatment and there fore, under certain circumstances, could have been re-treated if such guidelines were followed closely.…”
Section: Discussionmentioning
confidence: 99%
“…2 In terms of radiographic success, if there is a reduction in the size of a pre-opera tive periapical radiolucency then it may be deemed a success in the absence of clinical signs and symptoms. 11 It has been suggested that the absence of clini cal signs and symptoms irrespective of satisfactory radiographic features indi cate success, while others state there must also be evidence of complete boney repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies have reported out comes achieved by different services in the UK, for example Peak et al 5 in a study of endodontic care provided by Royal Air Force dentists reported that 88% of root fillings placed less than 2 mm from the apex had successful out comes, but overfilled teeth had a slightly lower success rate (75%) than underthose teeth which had been restored A research assistant visited all prac filled teeth (78%). Smith et al 6 in a by other means. tices and photocopied the clinical notes study of patients attending the Eastman Dental Hospital reported similar fi gures with 87% success rate for root fi llings placed less than 2 mm from the apex, 75% for those teeth root fi llings beyond the apex and 77% for those teeth with short root fillings.…”
Section: Introductionmentioning
confidence: 99%